The SAGE Handbook of Management Learning, Education and Development 2009
DOI: 10.4135/9780857021038.n9
|View full text |Cite
|
Sign up to set email alerts
|

Developing Leaders: Teaching about Emotional Intelligence and Training in Emotional Skills

Abstract: By the close of the twentieth century, the volume of literature addressing emotion in organizational settings stepped up even further, including special issues of journals (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 76 publications
(121 reference statements)
1
12
0
1
Order By: Relevance
“…Our findings suggest that managers could reduce exhaustion by actively seeking to encourage deep acting by team members. Previous studies have demonstrated that training can help individuals be more aware of their emotions and employ different emotional labor strategies (Ashkanasy, Dasborough, & Ascough, ; Totterdell & Parkinson, ). Therefore, seminars and training that discuss the personal and professional benefits of deep acting and provide strategies for genuinely changing one's feelings during difficult situations provide promising methods to increase individual deep acting.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that managers could reduce exhaustion by actively seeking to encourage deep acting by team members. Previous studies have demonstrated that training can help individuals be more aware of their emotions and employ different emotional labor strategies (Ashkanasy, Dasborough, & Ascough, ; Totterdell & Parkinson, ). Therefore, seminars and training that discuss the personal and professional benefits of deep acting and provide strategies for genuinely changing one's feelings during difficult situations provide promising methods to increase individual deep acting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that training interventions provide means to enhance emotional competence at work. In line with this, writings on emotional intelligence have argued that emotional abilities can be taught and developed (Pool & Qualter, 2012), that training can improve individuals' wellbeing and work performance (Schutte et al, 2013;Clarke, 2010a), and that education can improve individuals' emotional information processing and emotional literacy (Ashkanasy et al, 2009). Related writings have indicated that training in emotional skills may promote pro-social responses (Kemeny et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Luthans et al (2008) found that positive capital in the workplace can be developed via a training intervention. Furthermore, emotional skills may be beneficial for leaders, especially within team contexts (Ashkanasy et al, 2009). A study by Clarke (2010b) showed the powerful role of team-based learning with regard to emotional intelligence in the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Debates continue about definitional issues (e.g., whether EI is a set of specific abilities or a broader mix of motivational and dispositional characteristics), appropriate measurement instruments (which depend on the definition and whether subjects self‐assess), and matters of mutability (that is, the extent to which EI can be taught). In educational settings (i.e., classroom research and teaching), Ashkanasy et al () assert that only the ability‐based approach of Salovey and Mayer should be used, except for comparison purposes. They also ascribe to its associated abilities test, the MSCEIT (Mayer, Salovey, Caruso Emotional Intelligence Test) (Mayer et al, ).…”
Section: Locating Emotion In the Classroommentioning
confidence: 99%